2015
DOI: 10.14737/journal.aavs/2015/3.5.259.268
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Etiology of Skin and Wound Infections along with Antibiogram Profiling in Reference to Emerging Antibiotic Resistance in Animals

Abstract: | The present study demonstrated bacterial etiology of skin affections and their antibiogram profiling of different animal species of various age groups. A total of 255 samples from cattle, buffalo, dogs, goats, sheep, camel and horses were collected over a period of two years (2012)(2013)(2014) from Mathura, (U.P.) India, and nearby surrounding areas. Clinical samples were collected from variety of skin disorders, subjected to laboratory isolation and identification as per standard protocols. The bacterial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
3
1
0
Order By: Relevance
“…Ampicllin/sulpactum 20 µg was the most effective antibiotic inhibiting the growth of Gram negative bacteria, ciprofloxacin 5 µg was fairly effective and tetracycline 30 µg did not inhibit the growth of Pseudomonas species. This was similar from the findings of Tiwari et al (2015) who found that chloramphenicol was among the highly sensitive drugs and conversely amoxycillin and ampicillin/sulbactum were resisted in most cases. Shuaib et al (2016) found out that ciprofloxacin (5 µg), amikamicin (30 µg), cephalexin (30 µg), and impenen (10 µg) efficiently inhibited the growth of most isolated bacteria in their study while cefotaxime, ampicillin/sulbactam (30 µg), bactricin (10 µg), ceftizoxime (30 µg) and amoxacillin (30 µg) were the less effective or totally ineffective antibiotics in inhibiting bacterial growth.…”
Section: Discussionsupporting
confidence: 90%
“…Ampicllin/sulpactum 20 µg was the most effective antibiotic inhibiting the growth of Gram negative bacteria, ciprofloxacin 5 µg was fairly effective and tetracycline 30 µg did not inhibit the growth of Pseudomonas species. This was similar from the findings of Tiwari et al (2015) who found that chloramphenicol was among the highly sensitive drugs and conversely amoxycillin and ampicillin/sulbactum were resisted in most cases. Shuaib et al (2016) found out that ciprofloxacin (5 µg), amikamicin (30 µg), cephalexin (30 µg), and impenen (10 µg) efficiently inhibited the growth of most isolated bacteria in their study while cefotaxime, ampicillin/sulbactam (30 µg), bactricin (10 µg), ceftizoxime (30 µg) and amoxacillin (30 µg) were the less effective or totally ineffective antibiotics in inhibiting bacterial growth.…”
Section: Discussionsupporting
confidence: 90%
“…It was reported that, not all the bacteria, which were isolated from a wound, are susceptible to the single antibiotic. The antibiotic sensitivity pattern of the bacteria, which were isolate, showed resistant against one or multiple antibiotic drugs [15] Similar results were also reported in the present study with the most resistant and susceptible bacteria was Shigella and S. aureus respectively. Moreover, it is also reported in this study that, ciprofloxacin was highly effective antibiotic against all the bacterial isolates and less effective against cephalexin whereas it is reported by [15] that, the highly sensitive antibiotics which are effective against the bacterial isolates from the wound were gentamicin, chloramphenicol, amikacin, gatiflaxacin and sparflaxacin.…”
Section: Susceptibility Of Isolated Organisms Against Different Antibioticssupporting
confidence: 91%
“…However, the least prevalent bacteria on the skin wound are Pseudomonas spp, E. coli, Clostridium spp, Shigella spp and Klebsiella spp. Similar results were also reported on the wounds of equines by [10, 13, 14].It is reported that, the growth of these bacteria are inhibited either due immunity of an animal against these bacteria, or micro-environment of the wound and competitive inhibition by other virulent microbes (Staphlococcus spp) [15]. In this study, the contaminated skin wound were most commonly found at the back area and both sides of abdomen.…”
Section: Susceptibility Of Isolated Organisms Against Different Antibioticssupporting
confidence: 88%
“…In this study, 31.82% of camel carcasses examined had internal lesions in the lungs; this was similar to the findings of Wareth et al (2014) from El-Warrak slaughterhouse, one of Cairo's primary abattoirs. Also, with Ahmed and Musa (2015) from Sudan, but lower than the reports of Tiwari et al (2015) as they recorded lesions in lungs with 59.7% from India. On the same way, Awol et al (2011) and Bekele (2008) who found lesions on 77.5% and 98.0% of the camel carcasses in Ethiopia respectively.…”
Section: Discussionmentioning
confidence: 60%